Agro-economic evaluation of potassium application in spring maize under early and late sown conditions (Bangladesh Journal of Scientific and Industrial Research, 2017)
Although the yield potential of spring maize is much higher than autumn maize but high temperature at anthesis stage is one of the main problems in spring maize especially in late sown conditions which caused a synchronous pollination, fertilization and grain formation. Early sowing of the crop seems an ideal solution to escape the heat period but low temperature causes poor seedling establishment. Both temperature extremes osmotic and oxidative stresses are major reasons of economical crop damage. Potassium application may lessen these oxidative damages and crop stand establishment of maize under semi arid conditions of Faisalabad. Observations on number of plants per unit area, cobs per plant, grains per cob, 100-grain weight, grain yield, grain protein and oil contents were recorded by using standard procedures. The net income and benefit cost ratio were calculated to evaluate the most economical and profitable potassium level. Sowing dates affected significantly number of plants, cobs per plant, grains and 100-weight, grain yield, grain protein and oil contents while potassium application considerably improved grain yield through increasing crop stand under both early and late sown conditions by ameliorating stresses. It is concluded that the benefit cost ratio of 100 kg ha-1 potassium application is only beneficial under early planting on 1st February.Bangladesh J. Sci. Ind. Res. 52(4), 295-302, 2017